Measuring the Level of Employee Engagement Using Q12 GALLUP: case Study in PT Safta Ferti - Putri, Vivi Linda; Welly, John (Journal of Business and Management, 2014)
Employee engagement is now becoming one of the popular measurement tool to diagnose the level of engagement in the company. Researcher interested in introducing engagement tools to start-up company that is currently using some HR practices are the recruitment and compensation. Employee engagement is developing models and quite a lot of models. But the author uses the earliest models which Q12 Gallup is relatively simpler more than the models that develop later. To measure employee engagement, Researcher using quantitative method with questionnaire for 39 respondents.The purpose of this final project is Identify factors that drive employee engagement in PT Safta Ferti. And Provide conclusion and of this research and give improvement recommendation based on the analysis results for PT Safta Ferti. To achieve the objective above the researcher using Q12 Gallup Theory, Aon Hewitt, and motivation theory by maslow. And to get the result the researcher using Methodology, Data Assessment and Analysis, Conclusion and Suggestion.And the conclusion of this research is three are new factor that drive of employee engagement in PT Safta Ferti, that are Career and development, Job Fit, and Social Support. By examining this research, researcher clarifies the process in which the key driver of employee engagement affects the level of employee engagement, and the result of this research is the most significant factor and the key driver factor for employee engagement in PT Safta Ferti is Career and Personal Development.